Medicinal plants with potential use in herbal antidepressant: a review (Research, Society and Development, 2021)
Medicinal plants have been widely used in formulations for several therapeutic indications. Some species have been studied for the treatment of psychic disorders such as depression, among them are Rhodiola rosea L., Crocus sativus L. and Hypericum perforatum L. The demand for herbal therapies has increased, which denotes the increasing relevance of this area. This article aims to identify the activity of the species highlighted as natural alternatives in the treatment of depression through a literature review involving articles between 2010 and 2020 taken from the Pubmed, Scielo and Lilacs platform. Of the species under study used for the alternative treatment of depression, three are in greater evidence, including: Hypericum perforoatum L. also known as Herb of Saint John; Rhodiola rosea L., for states of depression in adults, there are some studies in animals and humans that suggest a putative antidepressant action; and Crocus sativus L., being one of the most expensive spices in the world, due to its cultivation and the way it is harvested. It is concluded that the species studied have extensive possibility of insertion in the treatment of depression, whether in adolescents, adults, elderly and even women breastfeeding or in depression after menopause. It is therefore expected that such results will contribute to the direction of further studies on the species concerned, guiding research in other areas that may not yet have been explored as well as other extracted compounds that may prove promising to the scientific community as an a ttherapeutic alternative.